2018
DOI: 10.1002/gps.5004
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of prescribing potentially inappropriate medications in a nationwide cohort of community dwellers with dementia receiving a comprehensive geriatric assessment

Abstract: Objective To identify the prevalence and predictors of prescribing potentially inappropriate medications (PIMs) in a nationwide cohort of community dwellers with dementia requiring complex care needs. Methods A cross‐matched data of the International Resident Assessment Instrument‐Home Care (9.1) (interRAI‐HC) and prescribing data obtained from the Pharmaceutical Claims Data Mart (Pharms) extract files for older adults (≥65 y) requiring complex care needs were utilized for this study. The 2015 Beers criteria w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 54 publications
3
10
0
1
Order By: Relevance
“…Previous findings seem contradictory as to the association between dementia and PIM use. Indeed, prior studies found that PIM use is common in older adults with Alzheimer's disease and related dementia, while other studies have observed the opposite . Finally, in our study, the risk of being persistent with PIMs at 1 year increased by 25% and 14% for individuals with diabetes and cardiovascular diseases, respectively.…”
Section: Discussionsupporting
confidence: 40%
“…Previous findings seem contradictory as to the association between dementia and PIM use. Indeed, prior studies found that PIM use is common in older adults with Alzheimer's disease and related dementia, while other studies have observed the opposite . Finally, in our study, the risk of being persistent with PIMs at 1 year increased by 25% and 14% for individuals with diabetes and cardiovascular diseases, respectively.…”
Section: Discussionsupporting
confidence: 40%
“…The requirement for proper discussion on limits of what treatment can achieve, and the specialist informing the GP adequately was identified as potentially leading to PIM. These findings are in line with those from previous research which emphasised the need for improved inter-professional communication, to address PIM, especially in palliative care [ 25 30 ].…”
Section: Discussionsupporting
confidence: 91%
“…However, whether or not prescribing anticholinergics is appropriate is something still unclear (López-Álvarez and Agüera Ortiz, 2019). In fact, a study using the Beers criteria found that 39.9% of elderly people with dementia on an outpatient basis were taking anticholinergic drugs classified as potentially inadequate (Bala et al, 2019).…”
Section: Prevalencementioning
confidence: 99%